The Role of Judges in Addressing the Failure of Divorce Mediation: Analysis Based on PERMA No. 1 of 2016 at the Ambarawa Religious Court - Rudi Nuradi (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
Divorce in Islamic law is, in principle, permissible yet strongly discouraged, and is regarded as a last resort when marital life can no longer be sustained. Islam emphasizes that, prior to divorce, both spouses should strive to maintain harmony and peaceful cohabitation, since marriage constitutes one of the most sacred and enduring bonds. The dissolution of marriage may occur either through ṭalāq or through a divorce lawsuit. In Indonesia, divorce may only be finalized before the Religious Court, after the court has attempted reconciliation but failed. This study aims to analyze (1) the factors contributing to the failure of mediation in divorce cases at the Ambarawa Religious Court, and (2) the strategies employed by judges to address and mitigate mediation breakdowns in such cases. This research is a field-based study using an empirical juridical approach, examining how legal norms are applied in practice to individuals, groups, and legal institutions. Primary data were obtained from judges of the Ambarawa Religious Court, while secondary data consisted of interviews with two judges and relevant documentary sources, including Supreme Court Regulation No. 1 of 2016. Data were collected through interviews and document analysis. The findings indicate that mediation failures in divorce cases at the Ambarawa Religious Court are primarily driven by the parties’ attitudes and strategic behavior such as unwillingness to communicate openly, a firm decision to divorce, and participation in mediation merely as a procedural formality to “win” the case often reinforced by third-party intervention, especially from parents. Judicial efforts to facilitate settlement are further constrained by heavy caseloads and the parties’ strong determination to proceed with divorce. The article recommends enhancing mediation quality at the Ambarawa Religious Court through more intensive training for judges/mediators, early screening of internal and external conflict drivers, and expanded pre- and post-mediation counseling services to increase the prospects of reconciliation and reduce divorce rates.